Duck hunter activity, success, and satisfaction on public hunting areas. Issue 4 (14th March 2022) - Gammonley, James H.; Runge, Jonathan P.
Abstract: Because hunting disturbance can influence local distribution of ducks and their availability to hunters, managers often limit access to hunting areas to improve hunting success and satisfaction. Few studies have quantified the effectiveness of public area access restrictions on duck hunter activity, harvest, or hunters' satisfaction with their hunting experience. We used a cross‐over design over 6 consecutive hunting seasons (2008–2009 through 2013–2014) on State Wildlife Areas (SWAs) in northeastern Colorado, USA, to compare the effects of restricted hunting access regulations and regulations without these restrictions on duck hunter activity, harvest success, harvest levels, and satisfaction. We also considered effects of SWA types, duck abundance, temperature, precipitation, use of equipment by duck hunting parties, and, for hunter satisfaction, hunting success, hunting parties' satisfaction with ducks seen, habitat conditions, crowding from other hunters, and SWA regulations. The number of days when duck hunters had access to restricted properties was about half that on unrestricted properties, and unrestricted properties were used by about twice as many duck hunting parties, but the mean number of hunting parties per available hunting day and mean party size were similar under the 2 types of regulations. Most (56%) duck hunting parties did not bag any ducks; hunting success (harvest of ≥1 duck by a hunting party) was best explained by a model that included a regulation type × hunting season interaction, a SWA type × month interaction, hunter density the previous day, an index of hunter investment (number of decoys used and whether dogs and calls were used), and temperature. Successful hunting parties harvested 1.92 ± 1.60 (SD) ducks/hunter/day (range = 0.1–7.0); the best model predicting the number of ducks harvested per hunter in successful parties included a regulation type × hunting season interaction, a SWA type × month interaction, hunter density the previous day, an index of hunter investment, temperature, and precipitation. Overall satisfaction of duck hunting parties with a day's hunt averaged 3.62 ± 1.20 based on a rank scale of 1 (very unsatisfied) to 5 (very satisfied), and was best explained by a model that included hunting party success; hunter investment; temperature; and satisfaction with duck numbers, habitat conditions, hunting regulations, and crowding. While greatly reducing days available for hunting, access restrictions were associated with improved chances of hunting parties successfully harvesting ≥1 duck in 5 of 6 hunting seasons, and substantially greater numbers of ducks harvested by hunters in successful parties in 1 of 6 hunting seasons. Restrictions did not have a strong direct effect on hunting parties' satisfaction with a day's hunt. Uncontrolled factors, including weather and use of equipment by hunters, had important influences on hunter success, harvest, and satisfaction. Managers should carefully assess hunting activity, hunter expectations and desires, and hunting area characteristics when considering access restrictions on public hunting areas. Abstract : Access restrictions on public hunting areas improved duck hunter success, but at the cost of reduced overall available hunting days, and with only marginal benefits to numbers of ducks harvested and hunters' satisfaction with a day's hunt. Managers must recognize that uncontrolled factors can have important influences on duck hunter harvest success and satisfaction, and should carefully consider management objectives and the desires of hunting constituents before implementing new access restrictions on public hunting areas.